Challenges of Developing Environmentally Friendly Transportation Infrastructure in Urban Areas - Muhamad Fajar Subkhan; Muhammad Taali (Politeknik APP Jakarta, 2025)
This research aims to identify and analyze the main challenges in developing environmentally friendly transportation infrastructure in urban areas, as well as to provide technical solutions based on calculations and scientific approaches in the field of transportation infrastructure engineering.The method used is a descriptive qualitative approach, with data collection through literature studies and field observations. The results of the study indicate that the development of environmentally friendly transportation in urban areas faces various challenges, ranging from budget constraints, weak coordination between sectors, to low public awareness. To strengthen the qualitative data, a system dynamics based on quantitative data is used with simulation 1 showing sustainability up to 30% of 100%, simulation 2 up to 25% of 100%, simulation 3 up to 20% of 100%, simulation 4 up to 15% of 100%, and simulation 5 up to 10% of 100%, thus showing that the factor that must be maximized is infrastructure and technology.